Kesesuaian Syariah Simpanan Sembako Terhadap Akad Wadiah di KSPPS Artha Yasmin Az-Zahra Jepara dalam Perspektif Fatwa DSN-MUI Nomor 02/DSN-MUI/IV/2000 - Sukma Dewi Pratama; Ahmad Fauzan Mubarok; Zahrotun Nafisah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Basic food items such as rice, eggs, sugar, and milk play a crucial role in people's lives, especially during the month of Ramadan, when demand for these commodities increases significantly. This condition encourages the habit of storing food, which then gives birth to innovations in basic food savings products in Islamic financial institutions. This study aims to examine the application of the wadiah contract in basic food savings products at the Artha Yasmin Az Zahra Sharia Savings and Loans and Financing Cooperative (KSPPS), with reference to the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) Number 02/DSN-MUI/IV/2000. The research method used is qualitative descriptive, with data collection techniques through interviews, observations, and documentation studies. The results of the study indicate that KSPPS Artha Yasmin Az Zahra applies the wadiah contract in the form of pure deposits, where the funds deposited by members are used to buy basic food items which will later be returned according to the agreed agreement. Although the implementation of the wadiah contract is in accordance with the provisions of the DSN-MUI fatwa, there are still obstacles, such as the lack of transparency in conveying information about the contract to members, which has the potential to affect their level of trust in this product. This study is expected to provide useful insights for KSPPS managers in improving the governance of basic food savings to be more in accordance with sharia principles and more transparent for its members.